Cation‐Exchange Enables In Situ Preparation of PbSe Quantum Dot Ink for High Performance Solar Cells. Issue 48 (17th October 2022) - Yuan, Mohan; Hu, Huicheng; Wang, Ya; Xia, Hang; Zhang, Xingchen; Wang, Binbin; He, Ziyang; Yu, Mengxuan; Tan, Yun; Shi, Zhaorong; Li, Kanghua; Yang, Xuke; et al.
Abstract: Lead selenide (PbSe) colloidal quantum dots (CQDs) are promising candidates for optoelectronic applications. To date, PbSe CQDs capped by halide ligands exhibit improved stability and solar cells using these CQDs as active layers have reported a remarkable power conversion efficiency (PCE) up to 10%. However, PbSe CQDs are more prone to oxidation, requiring delicate control over their processability and compromising their applications. Herein, an efficient strategy that addresses this issue by an in situ cation‐exchange process is reported. This is achieved by a two‐phase ligand exchange process where PbI2 serves as both a passivating ligand and cation‐source inducing transformation of CdSe to PbSe. The defect density and carrier lifetime of PbSe CQD films are improved to 1.05 × 10 16  cm −3 and 12.2 ns, whereas the traditional PbSe CQD films possess 1.9 × 10 16  cm −3 defect density and 10.2 ns carrier lifetime. These improvements are translated into an enhancement of photovoltaic performance of PbSe solar cells, with a PCE of up to 11.6%, ≈10% higher than the previous record. Notably, the approach enables greatly improved stability and a two‐month stability is successfully demonstrated. This strategy is expected to promote the fast development of PbSe CQD applications in low‐cost and high‐performance optoelectronic devices. Abstract : PbI2 ‐capped PbSe colloidal quantum dot ink is prepared via in situ exchange of CdSe into PbSe. This process has good processability and is easily carried out for PbSe ink preparation. Employing this ink for a solar cell fabrication, device shows a record efficiency of 11.6% with impressive air and light soaking stability.